Land-use planning based on ecosystem service assessment: a case study in the Southeast Pampas of Argentina - Barral, María Paula (2012)
A methodological protocol of strategic environmental assessment was developed to incorporate the valuation of ecosystem services in land use plans. The protocol was applied in rural land planning at Balcarce, a department representative of the Southeast Pampas Region (Argentina). The ecosystem services approach was used as valuation criteria of the 14 principal ecosystems classified in the studied area, where agricultural is the predominant economic activity. The provision of seven principal ecosystem services related to regulation functions or food production was estimated for each ecosystem using a set of indicators integrating climatic, vegetation and terrain variables. The assessment of land use changes showed a significant increase in agriculture in the past 20 years, which affected mainly natural grasslands. The environmental impact of this replacement varied according to the ecosystem and the area. Hills and riparian zones were identified as key areas for grassland conservation in order to provide regulation ecosystem services in agricultural landscapes. On the basis of this analysis, a preliminary zoning was proposed, aimed to retain critical support and regulation ecosystem services without significantly sacrificing food production for humans. Strategic environmental assessment based on ecosystem services appears as a powerful tool to prevent negative environmental costs of land use plans which can remain unnoticed under traditional environmental impact assessment techniques.